ANALSIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETAATAN WAJIB PAJAK ORANG PRIBADI DALAM MELAPORKAN SURAT PEMBERITAHUAN TAHUNAN - Meilinda Stefani Harefa (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2019)
The purpose of the research is to analysis factors that affect individual taxpayer compliance. In this research there are four factors on tax compliance, namely: awareness of taxpayer, tax knowledge, quality of services and tax penalties. The data of this study were obtained by distributing questionnaires with a sample of 84 taxpayers at Tax Office of Medan City. The research method used is multiple regression. The conclusion of this study is that each independent variable namely awareness of taxpayer, tax knowledge, quality of services, and tax penalties has a positive and significant impact on the compliance of individual taxpayers. Key words: awareness of taxpayer, tax knowledge, quality of services, tax penalties, and tax compliance.